The Practice of Paying Takaful Benefits in Malaysia: Implications of the Islamic Financial Services Act 2013: (Praktis Pembayaran Manfaat Takaful di Malaysia: Implikasi Pascaakta Perkhidmatan Kewangan Islam 2013) (Kanun: Jurnal Undang-undang Malaysia, 2016)
This article analysis the provisions of the Islamic Financial Services Act 2013 (IFSA 2013) which details several aspects including the payment of takaful (Islamic insurance) benefits, including the naming of trustees (property administrators) or beneficiaries of conditional hibah (gifts) which were not dealt with in detail in the Takaful Act 1984. This study employs the approach of qualitative content analysis. The study reveals that the shift from the Takaful Act 1984 to IFSA 2013 not only standardized the practices of paying takaful benefit in Malaysia but also provides options for Muslim participants in the distribution of takaful benefits. This gives takaful products an edge over conventional insurance products as it offers risk-management products to both Muslims and non-Muslims in Malaysia.Keywords: takaful benefit payments, Islamic Financial Services Act 2013, Takaful Act 1984, Malaysian takaful industry